Effectiveness of Cordia verbenacea and Propolis as Irrigation Solution on the Bond Strength of Filling Material to the Root Dentin: In vitro Study - , Gabriel Kennedy Barroso; , Kaio Henrique Soares; , Ângelo Fonseca Silva; , Thiago Fonseca-Silva; , Carolina Carvalho de Oliveira Santos (Archives of Current Research International, 2024)
Introduction: Endodontic treatment aims to eliminate pathological microbiota from root canals to prevent or treat infections in periapical tissues. Irrigation is a crucial step in this process, serving important mechanical, chemical, and biological functions. Objective: This study aimed to evaluate the effect of irrigation with Cordia verbenacea and propolis solutions compared to chlorhexidine and sodium hypochlorite on the bond strength of the filling material to the root dentin. Materials and Methods: This In vitro experimental study involved 40 healthy human premolars subjected to the push-out test. The teeth underwent decoronation, followed by biomechanical endodontic preparation using mechanized files. The teeth were then divided into four groups according to the irrigating solution: NaOCl 5.25%, chlorhexidine 2%, aqueous extract of Cordia verbenacea and aqueous extract of propolis. Data were statistically analyzed using analysis of variance and the Post-Hoc Bonferroni test. Results: The group irrigated with propolis showed greater resistance to the push-out test in the middle and apical thirds when compared to the other groups (p<0.05). There were no statistically significant differences among the other groups. Conclusion: Irrigation with propolis extract resulted in higher bond strength of the obturating material to the root canal, while irrigation with Cordia verbenacea showed similar results to chlorhexidine and sodium hypochlorite.